Implementasi Sistem Infomasi Berbasis Elektronik Melalui SIPD dalam Proses Perencanaan Pembangunan di Kabupaten Lebak - Wilansari Wilansari; Ipah Ema Jumiati; Leo Agustino (Jurnal Ranah Publik Indonesia Kontemporer (Rapik), 2022)
This research is conductedto analyze the implementation of the Regulation of the Minister of Home Affairs of the Republic of Indonesia Number 70 Year2019 in the Development Planning Process in Lebak Regencyby exploringthe driving and inhibiting factors.. The theory used is the theory of public policy implementation according to Van Metter and Van Horn with six variables, namely: size and policy objectives, resources, characteristics of implementing agents, attitudes or tendencies of implementers, communication between organizations and implementing activists, and the economic, social environment., and politics. The research method used is qualitative. The results of the study show that there are still several obstacles and problems in the Implementation of the Regulation of the Minister of Home Affairs of the Republic of Indonesia Number 70 Year2019 including: (1) There is no attachment regarding standardization of data for regional government needs; (2) the sectoral ego of the Ministry of Home Affairs to emerge theissue obout rules and applications; (3) the application reliability has not been tested in terms of structure, content, and network availability.